Dopamine D4 receptor gene and religious affiliation correlate with dictator game altruism in males and not females: evidence for gender-sensitive gene × culture interaction - Jiang, Yushi; Bachner-Melman, Rachel; Chew, Soo Hong; Ebstein, Richard P. (Frontiers in Neuroscience, 2015)
On a large sample of 2288 Han Chinese undergraduates, we investigated how religion and DRD4 are related to human altruistic giving behavior as measured with the Andreoni-Miller Dictator Game. This game enables us to clearly specify (non-)selfishness, efficiency, and fairness motives for sharing. Participants were further classified into religious categories (Christian, Buddhist-Tao, and No Religion) based on self-reports, and genotyped for the dopamine D4 receptor (DRD4) gene exon III VNTR. Our analysis revealed a significant interaction between religion and DRD4 correlated with giving behavior solely among males: Whereas no significant association between religion and sharing decisions was observed in the majority 4R/4R genotype group, a significant difference in giving behavior between Christian and non-Christian males was seen in the non-4R/4R group, with Christian men being overall more altruistic (less selfish and fairer) than non-Christian men. These results support the vantage sensitivity hypothesis regarding DRD4 that the non-4R/4R ‘susceptibility’ genotype is more responsive to a positive environment provided by some religions.